An ethnobotany of the Lukomir Highlanders of Bosnia & Herzegovina. Issue 1 (December 2015) - Ferrier, Jonathan; Saciragic, Lana; Trakić, Sabina; Chen, Eric; Gendron, Rachelle; Cuerrier, Alain; Balick, Michael; Redžić, Sulejman; Alikadić, Emira; Arnason, John
Abstract Background This aim of this study is to report upon traditional knowledge and use of wild medicinal plants by the Highlanders of Lukomir, Bjelašnica, Bosnia and Herzegovina (B&H). The Highlanders are an indigenous community of approximately 60 transhumant pastoralist families who speak Bosnian(Bosanski) and inhabit a highly biodiverse region of Europe. This paper adds to the growing record of traditional use of wild plants within isolated communities in the Balkans. Methods An ethnobotanical study using consensus methodology was conducted in Lukomir in Bjelašnica's mountains and canyons. Field work involved individual semi-structured interviews during which informants described plants, natural product remedies, and preparation methods on field trips, garden tours, while shepherding, or in settings of their choice. Plant use categories were ranked with informant consensus factor and incorporated into a phylogenetic tree. Plants cited were compared to other ethnobotanical surveys of the country. Results Twenty five people were interviewed, resulting in identification of 58 species (including two subspecies) from 35 families, which were cited in 307 medicinal, 40 food, and seven material use reports. Individual plant uses had an average consensus of five and a maximum consensus of 15 out of 25. There were a number of rare and endangered species used as poisons or medicine that are endemic toFlora Europaea and found in Lukomir. Ten species (including subspecies) cited in our research have not previously been reported in the systematic ethnobotanical surveys of medicinal plant use in B&H: (Elymus repens (L.) Gould, Euphorbia myrsinites L., Jovibarba hirta (L.) Opiz, Lilium bosniacum (Beck) Fritsch, Matricaria matricarioides (Less.) Porter ex Britton, Phyllitis scolopendrium (L.) Newman, Rubus saxatilis L., Silene uniflora Roth ssp.glareosa (Jord.) Chater & Walters, Silene uniflora Roth ssp. prostrata (Gaudin) Chater & Walters, Smyrnium perfoliatum L.). New uses not reported in any of the aforementioned systematic surveys were cited for a total of 28 species. Thirteen percent of medicinal plants cited are endemic:Helleborus odorus Waldst. et Kit., Gentiana lutea L., Lilium bosniacum (Beck) Fritsch, Silene uniflora Roth ssp.glareosa (Jord.) Chater & Walters., Silene uniflora Roth ssp.prostrata (Gaudin) Chater & Walters, Salvia officinalis L., Jovibarba hirta (L.) Opiz, andSatureja montana L. Conclusions These results report on the cohesive tradition of medicinal plant use among healers in Lukomir, Bosnia and Herzegovina. This work facilitates the community's development by facilitating local and international conversations about their traditional medicine and sharing insight for conservation in one of Europe's most diverse endemic floristic regions, stewarded by one of Europe's last traditional Highland peoples.